PERANAN PENDIDIKAN TERBUKA DAN JARAK JAUH DALAM MENINGKATKAN DAYA JANGKAU PENDIDIKAN TINGGI DI ASIA TENGGARA - Endang Nugraheni (LPPM Universitas Terbuka, 2009)
Accesibility and quality of education especially for higher education has been a constant concern for the developing countries including South East Asian countries. Open and distance education (ODL) system seems to be the answers for increasing accesibility because of its cost effectiveness and flexibility. This article addresses efforts in expanding the quantity and improving quality in some ODL institutions in South East Asia. This article also presents specific experience and lessons learnt from Indonesia, particularly Universitas Terbuka, in responding to the issues of quantity expansion, improvement of student participation in higher education, and continual quality improvement of ODL.